SOSIALISASI PERSYARATAN TANGKI SEPTIK DALAM RANGKA PENCEGAHAN PENYAKIT DI DAERAH DEPOK - Dewi Syavitri; Silia Yuslim; Budi Wijaya; Firman Herdiansyah; Muhammad Khadafi; Fahd Nibel Athallah (Universitas Trisakti, 2021)
Community Service (PkM) aims to provide understanding to the community in the Depok area, which has been affected by the Hepatitis A pandemic outbreak, regarding the importance of maintaining the distance between septic tanks and drilled wells in order to prevent diseases caused by contaminated water. The method used is to provide socialization of the Minister of Health Regulation no. 3 of 2014 and SNI 2398:2017 to PKK women, cadres, in Gandul Village, Cinere Depok District, regarding septic tanks, manufacturing requirements and their distance to clean water sources. Based on the pre and post tests carried out, it showed that all PkM participants already understood the importance of the requirements for making speptic tanks and setting the distance between the septic tank and clean water wells. However, to apply in the field still requires assistance. The implications of this PkM provide an opportunity for extension workers to research further about groundwater conditions in Gandul Village in order to provide solutions for the community to anticipate the presence of existing fecal waste so as not to pollute the existing ground water